The Crystal Structure of the New Layered Alloy (CuGa)0.52TaSe2 Studied by SEM, DTA, and XRPD - Delgado, Gerzon E.; Durán, Sonia; Aitken, Jennifer A.; Muñoz, Marcos; Grima-Gallardo, Pedro (Orbital: The Electronic Journal of Chemistry, 2021)
The new (CuGa)0.52TaSe2 alloy was synthesized by the melt and annealing technique and studied by SEM, DTA, and XRPD techniques. Its structure has been refined by the Rietveld method using X-ray powder diffraction data. This compound crystallizes in the hexagonal space group P-6m2 (Nº 187) with unit cell parameters a = 3.648(2) Å, c = 13.568(4) Å, V = 156.4(1) Å3, Z = 2. The crystal structure is based on the MoS2-type of stacking of TaSe2 layers with a partial ordering of Cu and Ga cations over the tetrahedral sites. The powder pattern was composed of 63.9% of the principal phase (CuGa)0.52TaSe2 and 26.3% of CuGaSe2, 9.8% of TaSe3, as the secondary phases.DOI: http://dx.doi.org/10.17807/orbital.v13i4.1559